The Continuum Between Hexagonal Planar and Trigonal Planar Geometries. Issue 44 (5th October 2022) - Garçon, Martí; Phanopoulos, Andreas; Sackman, George A.; Richardson, Christopher; White, Andrew J. P.; Cooper, Richard I.; Edwards, Alison J.; Crimmin, Mark R.
Abstract: New heterometallic hydride complexes that involve the addition of Mg−H and Zn−H bonds to group 10 transition metals (Pd, Pt) are reported. The side‐on coordination of a single Mg−H to Pd forms a well‐defined σ‐complex. In contrast, addition of three Mg−H or Zn−H bonds to Pd or Pt results in the formation of planar complexes with subtly different geometries. We compare their structures through experiment (X‐ray diffraction, neutron diffraction, multinuclear NMR), computational methods (DFT, QTAIM, NCIPlot), and theoretical analysis (MO diagram, Walsh diagram). These species can be described as snapshots along a continuum of bonding between ideal trigonal planar and hexagonal planar geometries. Abstract : The isolation and bonding analysis of a series of heterometallic hydride complexes shows they have subtly different bonding geometries. These compounds can be described as snapshots along a continuum of bonding between trigonal and hexagonal planar geometries.